Gender and Political Dynamics: A Comparative Study of Joseph Stalin and Vladimir Putin's Eras. (2nd January 2020) - Karim, Aleena
ABSTRACT: This paper questions the innateness associated with the gender roles and gender relations while providing the comparative analyses of the gender roles practised in the political eras of Joseph Stalin (1922–1953) and the most recent ruling time period of Vladimir Putin (2012–present). It is further emphasized that gender roles and gender relations are not static but variable in nature. This is because they are further dependent, for their practice, upon the external factors - the variables-classified as the political factors in this research. The reason to select Russia as the case study is the silence it has been observing on the gender platforms across the world. The paper employs Judith Butler's, the American philosopher and gender theorist, gender perspective, in particular, that one's gender role cannot be solely defined on the basis of one's biological characteristics. In fact, gender roles are the relational complexes which are the result of the influence generated by the external factors on one's individual gender identity. Hence, this research concludes on the point that the changing political eras in Russia serve as the key factor for either a pre-discursive and innate or a contextualized outlook of the gender roles.